MANAGEMENT OF REPEAT BREEDING UNDER FIELD CONDITIONS USING HORMONAL AND NON-HORMONAL DRUGS IN COWS - KUMAR, RAJESH; DHAMI, A J; BUTANI, M G; KAVANI, F S; SARVAIYA, N P; KILLEDAR, ANKITA (The Indian Journal of Animal Reproduction, 2023)
A study was carried out on 4 7 repeat breeding crossbred cows to evaluate the therapeutic efflcacyof various hormonal and non-hormonal drugs in improving their reproductive efficiency. 19, 11 and 9cows were treated with 0.02 mg GnRH (Receptal 5 ml i/m), just after Al, 500 mg of hydroxy-progesteronecap~oate (Duraprogen 2 ml i/m)'on day 4 post-Al, and antibiotics ceftriaxone (lnj. Velacef 2 gm) orcephalexin (Lixen 4 gm) i/ut 12-24 hrs post-Al, respectively. The overall conception rate was 73.68,I.·8'1 .82 and 77.77 %, respectively, (P
Keywords: Repeat breeding cows; Hormonal/Non-hormonal therapy